Developing market-oriented politics in Nigeria: A review of the 2019 presidential election - Olanrewaju O. Akinola; Ibrahim A. Adekunle (African Governance and Development Institute (AGDI), 2020)
The 2015 presidential elections in Nigeria were unique in many facets. Apart from being the first time an incumbent candidate of a ruling party lost to the candidate of the opposition party, it was also the first presidential election that did not go through expensive and rigorous post-election litigations processes. From the political marketing point of view, we argued that the marketoriented approach, the purposeful, coordinated, and strategic use of marketing communication media and tools contributed to the success of APC at the 2015 presidential polls. The success story of the 2015 election gave rise to the evolution of voter-centric election campaigns, indicating that marketing and communication professionals and strategies, rather than violence and electoral fraud, have dominated and could dictate the outcomes of future elections in Nigeria. Based on the foregoing, this study reviewed the 2019 presidential election (the next election after the 2015 general election in Nigeria) to ascertain if that anticipated better tomorrow is here. We rely on experts' interviews, direct observations, and secondary materials to confirm if the political landscape in Nigeria is market-driven. Findings revealed that the 2019 presidential election was extremely monetised, violent, and fraught with all manners of electoral misconducts such that are antithetical to the principles and practice of political marketing. We aver that electioneering in Nigeria is not market-driven and voter-centric.
Keywords: 330; Political Marketing; Democracy; 2019 Election; Market-Orientation; Nigeria